The Impact of Civil Law Reforms on Environmental Protection Initiatives - Jorge Luis Borges; Ricardo Piglia; Samanta Schweblin (International Forum of Researchers and Lecturers, 2024)
Environmental protection is increasingly becoming a priority in civil law reforms as governments recognize the need for sustainable development. This article examines recent civil law reforms aimed at bolstering environmental protection initiatives. It assesses the effectiveness of new legal measures, such as stricter liability for pollution and enhanced citizen rights for environmental advocacy. The findings suggest that while progress has been made, further reforms are needed to ensure effective implementation and enforcement. Recommendations are provided for policymakers to enhance the impact of civil law on environmental protection.